Use of ChatGPT to Improve Digital Enterprise Business Performance - Hendrawan, Muhammad Ridho Nur Alamsyah; Ismail, Nurizal (Department of Management, Faculty of Economics, Universitas Islam Sutan Agung, Semarang, 2024)
Artificial intelligence-based technologies, such as Chat GPT, are increasingly being applied in online businesses to improve business performance in businesses. This research uses qualitative research to explore the impact of using GPT Chat on online business performance among digital business actors using a phenomenology approach. In this research, data collection was carried out using a structured interview method. The data analysis method used in this research is thematic analysis. The results of data analysis show that using ChatGPT helps complete tasks faster, makes it easier to complete tasks, helps acquire new knowledge, helps acquire new skills, helps find innovative ideas, using ChatGPT can improve your service delivery to customers, helps identify problems faced by the company, helps in making decisions for the company, helps make better quality decisions and helps make more effective decisions.